Orangutan (Pongo pygmaeus wurmbii) human-oriented behavior at the Lamandau Wildlife Reserve, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Amalia N, Fajarallah DP, Atmoko SSU. 2021. Orangutan (Pongo pygmaeus wurmbii) human-oriented behavior at the Lamandau Wildlife Reserve, Indonesia. Biodiversitas 23: 396-402. Unlike other conservation efforts, rehabilitation and reintroduction face different challenges due to humans' role in developing orphaned orangutans. Long-term interactions between orangutans and humans in captivity will gradually encourage orangutans to shape and increase human-oriented behavior (interest in humans). The Lamandau Wildlife Reserve (Lamandau WR) applies the soft-release method for the orangutan release process. Additional feed is provided every day. The correlation between animal-human interactions as part of the conservation efforts evaluation is essential to study. This study aimed to analyze the human-oriented behavior of the orangutan population in the Lamandau WR based on the observation sites (camp, feeding site, and forest) and the age-sex class of orangutans. This study also identified the factors that affected them. The study was conducted for five months (July-November 2019). During the observation, the factor of current age was suspected to affect human-oriented behavior. Human-oriented behavior is divided into three categories based on the orangutans' response: approaching, avoidance, and no response. The highest rates of human-oriented behavior in orangutans were approaching category. The highest promoting behavior was noticed at the camp and feeding site, especially young orangutans and mothers. Interest in humans can be explained by the 'captive effect' phenomenon where captive orangutans are more likely to independently explore the novelty (unfamiliar objects/foods) than their wild counterparts.
Keywords: Camp; Feeding site; Human-oriented; Lamandau WR; Orangutan; Reintroduction